Variations of terrigenous material discharges in the South Okinawa trough and its relation to the East Asian summer monsoon since the last millennium - Chen, Jinxia; Li, Tiegang; Qingyun, Nan (Journal of China University of Geosciences, 2009)
The top part of a giant IMAGE core MD05-2908 taken from the South Okinawa Trough was investigated for the sake of understanding the climate evolution in Donghai seacoast areas since the last millennium. Sporopollen and organic carbon isotope records of bulk sediments were used as proxies to trace the climate variations and terrigenous materials discharges. Time series were demarcated by 4 AMS 14 C dating ages. Comprehensive data of sporopollen and carbon isotopic composition, together with the paleoenvironmental records show that in the South Okinawa Trough the terrigenous material discharges fluctuated obviously for the past 1000 years. Three relatively high terrigenous material discharge periods, corresponding to 1100-1040 a BP, 960-880 a BP and 800-480 a BP respectively and two quite low terrigenous material discharge periods, namely, 1040-960 a BP and 480-230 a BP, can be identified from our records. In comparison with the stalagmite delta (super 13) C records(which were used to trace the East Asian Summer Monsoon) from Buddha Cave, Shaanxi Province, we found that the variations of terrigenous material discharges might be related closely to variations of the East Asian Summer Monsoon(EASM). Weaker EASM resulted in a convergence rain belt and longer residence time in the South China regions, which increased the efficiency of weathering and denudation of the source area. Moreover, increased rainfall enhanced the land runoff and as a result more terrigenous materials were transported to the South Okinawa Trough.
id: 1948; Source type: scholarlyjournals; Object type: Article; Copyright: GeoRef in Process, Copyright 2011, American Geosciences Institute. After editing and indexing, this record will be added to Georef.; CSAUnique: 600756-13; AccNum: 600756-13; ISSN: 1000-2383; Peer Reviewed: true